Pembentukan Karakter Anak Dengan Pendekatan Berbasis Pendidikan Al-Qur’an - Ahmadi, Ahmadi (Tarbiyah STAIN Sorong, 2018)
It is natural that morality is a very important foundation in human life. So the formation of character (morals) is part of the main mission of the Prophet Muhammad. Therefore in forming character, it is important to have a formulation of the organization of Islamic education as character education. In formulating it back to the source of Allah's guidance in His shari'a. This study aims to determine the character building of children with the approach of al-Qur'an based education. The type of research used is descriptive qualitative research (library research). The conclusion of this study is the education of the Qur'an gradually bringing someone to knowledge who finally was able to practice and reflect in everyday life into a praiseworthy personality. To get a proper understanding of the study of the Qur'an, it is necessary to approach it to reflect what is being read.